Directed neutrophil migration to IL-8 is increased in cystic fibrosis: a study of the effect of erythromycin. Issue 1 (1st January 2001) - Brennan, S; Cooper, D; Sly, P D
Abstract : BACKGROUND: The aim of this study was to compare neutrophil migration in cystic fibrosis (CF) and non-CF populations and to investigate the effect of erythromycin on directed migration of neutrophils (PMNs) in CF. METHODS: PMNs were isolated and their migratory capacity in response to interleukin-8 (IL-8) or f-Met-Leu-Phe (fMLP) in the presence or absence of erythromycin (1–100 μg/ml) was assessed. RESULTS: CF derived PMNs showed significantly increased migration to IL-8 but not to fMLP compared with non-CF PMNs. Erythromycin had no significant effect on migration responses to IL-8 and in vitro exposure of PMNs to erythromycin had no effect. CONCLUSIONS: CF derived PMNs show higher migratory responsiveness to IL-8 but not to fMLP, suggesting that CF PMNs may be "primed" to IL-8 which is significantly increased in CF serum compared with non-CF serum. Treatment with erythromycin had no significant effect on PMN migration in vitro.